VEGF and odontoblast-like cells: Stimulation by low frequency ultrasound - Scheven, B.A.; Man, J.; Millard, J.L.; Cooper, P.R.; Lea, S.C.; Walmsley, A.D.; Smith, A.J. (Archives of oral biology, 2009)
Vascular endothelial growth factor (VEGF) has been implicated in the regulation of dental pulp and dentine repair. Therapeutic ultrasound was shown to be effective for fracture repair. We investigated whether low frequency ultrasound influences the production of VEGF by odontoblast-like cells. Moreover, we examined the direct effects of VEGF on odontoblast-like cell proliferation. MDPC-23, an established odontoblast-like cell line, was exposed to increasing intensities of 30 kHz ultrasound using an ultrasonic tip probe. After 24 h cell culture, WST-1 analysis of cell viability and number showed a dose-dependent decrease in the number of viable cells with increasing ultrasound power. However, the relative concentration of VEGF as analysed by ELISA and normalised to cell number was significantly increased in the culture supernatants indicating an ultrasound-induced stimulation of odontoblastic VEGF secretion. Analysis of VEGF gene expression by sqRT-PCR revealed the expression of the main VEGF isoforms in the MDPC-23 cells, i.e. VEGF 120 and VEGF 164 as well as to a minor extent VEGF 188. Low power ultrasound increased gene expression of all VEGF isoforms. Addition of recombinant VEGF to the cell cultures significantly stimulated cell proliferation. Gene expression of the VEGF receptors Flt1/VEGFR1 and KDR/VEGFR2 was detected in the MDPC-23, suggesting the possibility that VEGF may act on the odontoblast-like cells in an autocrine manner. Our results indicate that ultrasound promoted VEGF expression and production by odontoblast-like cells and that VEGF may have autocrine effects on these cells. It is proposed that ultrasound may influence odontoblast activity and dentine repair by modulating production of endogenous growth factors in the dentine-pulp complex.